Middle leaders' perceptions and actions on assessment: the technical, tactical and ethical. (1st January 2020) - Tay, H.Y.; Tan, K.H.K.; Deneen, C.C.; Leong, W.S.; Fulmer, Gavin W.; Brown, Gavin T. L.
ABSTRACT: Assessment leadership has often been associated with school leaders (SL), comprising principals and vice-principals. This study aimed to examine the under-researched assessment leadership role of Middle Leaders (ML) instead. Data was drawn from a larger, mixed-methods project that involved a self-report questionnaire administered to principals, MLs and teachers across twelve schools as well as observations and one-to-one interviews with one ML each from seven schools. The study found that Assessment for Learning (AfL) has gained some traction among the MLs because of the assessment practices they value, they rate more highly those more associated with AfL, particularly Student Involvement and Engagement; compared with Grading / Reporting which is more directly related to summative assessments. In particular, the study found that MLs used three dominant approaches in their assessment leadership – Technical, Tactical and Ethical. Technical leadership was seen in their focus on overseeing the technical aspects of assessment, particularly in aligning assessment to curriculum goals and expecting teachers to deliver on grading and reporting, for accountability purposes. In response to various tensions encountered in their work, the MLs also exercised tactical and ethical leadership. These findings highlight how MLs' perceptions and actions are influenced by and mediate policy implementation in schools.